Perancangan dan Implementasi Pengaturan Kecepatan Motor Induksi Tiga Fasa Berbasis Logika Fuzzy terhadap Variasi Beban pada PLC Mitsubishi FX3U - Nanang Rohadi; Liu Kin Men; Akik Hidayat (Jurnal Nasional Teknik Elektro dan Teknologi Informasi, 2026)
Three-phase induction motors are extensively deployed in industrial automation due to their robustness, simplicity, and efficiency. Nevertheless, maintaining speed stability under dynamically varying loads remains a significant control challenge. This study investigated the design and implementation of a fuzzy logic-based speed control system fully embedded within a Mitsubishi FX3U-64M programmable logic controller (PLC), eliminating the dependency on external software platforms. The system integrated a rotary encoder for real-time speed feedback, an FX2N-2DA digital-to-analog converter for signal output, and a Mitsubishi FR-E520 inverter for frequency and voltage regulation. The fuzzy controller utilized two input variables, speed error and rate of change, which were fuzzified and processed through a Mamdani-type inference mechanism. All fuzzy operations, including rule evaluation and centroid-based defuzzification, were executed using ladder diagram programming via GX Works2. Experimental validation was performed across five speed references (300 to 1200 rpm) and varying mechanical loads (0.5–1.5 kg). The controller consistently achieved steady-state errors below 1% in no-load conditions and below 0.5% under load, with recovery times ranging from 1.5 to 6.75 s. These results demonstrate that the proposed PLC-based fuzzy controller provides a responsive, accurate, and fully integrable solution for real-time industrial motor speed regulation under variable operating conditions.